Food and Memory as Portrayed in Crying in H Mart Memoir by Michelle Zauner - Melano, Daniel; Saragih, Mike Wijaya (Journal of Language and Literature, 2025)
Crying in H Mart, a memoir by Michelle Zauner, describes how Michelle, as the main character, recalls her memories through Korean food. After her mother died, she tried to keep connected with her mother through the activity that they did together related to Korean food. Some activities included cooking, eating, visiting restaurants, preparing food, etc. While reconnecting to her memory, Michelle also tried to keep connected with the heritage that her mother had given to her, which is a Korean identity. This study aims to show the connection between food, memory, and culture in the Crying in H Mart memoir. The writers use a descriptive qualitative method with a close reading of the memoir.  Abarca's concept of Holistic Culinary is needed to analyze the connection between food, memory, and culture portrayed in the memoir. The result shows that the connection of food, memory, and culture enabled Michelle to reconnect to her experience with her family, especially her mother. From reconnecting to her past, Michelle's emotions were triggered. The way Michelle reconnected to her past makes her keep connected with her mother's heritage and explore the Korean culture more through interacting with Korean people, doing self-cultural exploration, and promoting Korean culture.